The Ecological Status and Distribution of Mangrove in Gujarat: A Systematic Review (International Journal of Scientific Research in Science and Technology, 2025)
Mangroves are the only species that survive in harsh conditions where no other species can survive. They mainly found at intertidal zones of tropical and sub-tropical regions of all over the world. They form a bridge between terrestrial and aquatic ecosystem and enables flow of energy between them. These woody species consist various adaptation in anatomy, physiology and morphology to survive in harsh environment conditions. This forest provides important and unique ecosystem good and services to human society as well as to coastal and marine ecosystem. Biotic pressure and natural calamities are the enemies of these ecosystems. Urbanisation and industrialization are the main cause of deforestation of the mangal. Due to pollution and over extraction caused by aquaculture, agriculture and urban development, large scale deforestation of these ecosystem has been recorded in past few decades. Intensive conservation efforts are needed to conserve these sensitive ecosystems. The ecology, diversity and distribution of mangroves in Glob, in India and particular in Gujarat has been reviewed in this paper. The data obtained from various literature of the authors had been analysed. Also, the importance, threats and conservation strategies to protect these ecosystems were also reviewed in briefly.
Keywords: Mangrove; Mangrove cover; Mangrove diversity; Mangrove distribution; Gulf of Kachchh